Gifted underachievers and factors affecting underachievement - Başlantı, Uğur. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2002., 2002)
The study aims to clarify the relationship between the characteristics of gifted underachievers at the university level and reasons for underachievement. Underachievement among gifted university students regarding their personality characteristics, home and parental variables, teacher and school related factors were examined. The students from Bogazici University in Istanbul, who have already demonstrated their intellectual ability and high academic performance in a selective and external standardized university entrance examination constituted the sample. SAAS-R (School Attitude Assessment Survey-Revised) instrument were administered to 91 underachievers to examine the reasons of underachievement. The instrument employed five sub-scales: Academic self-perceptions, attitudes toward teachers, attitudes toward school, goal valuation and motivation/self-regulation. In addition to an instrument, interviews were made with 30 underachievers to make further explanations and to check the findings obtained from the SAAS-R instrument.Findings indicated that the five sub-scales of the SAAS-R instrument can be used to explain the reasons of underachievement among gifted underachievers at Bogazici University. Among the five sub-scales; motivation seemed to be the most exploratory factor. On the other hand, results from the interview indicated that students' responses were parallel with the findings from the SAAS-R instrument. Recommendations based on the results of the study for the teachers, advisors, counselors, researchers and families are discussed.
Keywords: Underachievers.; Gifted children -- Education.; Exceptional children.